2003
DOI: 10.1063/1.1610240
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of random chaotic maps with an invariant measure

Abstract: Hierarchy of one and many-parameter families of random trigonometric chaotic maps and one-parameter random elliptic chaotic maps of cn type with an invariant measure have been introduced. Using the invariant measure (Sinai-Ruelle-Bowen measure), the Kolmogrov-Sinai entropy of the random chaotic maps have been calculated analytically, where the numerical simulations support the results .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…
AbstractWe present hierarchy of one and many-parameter families of elliptic chaotic maps of cn and sn types at the interval [0,1]. It is proved that for small values of k the parameter of the elliptic function, these maps are topologically conjugate to the maps of references [1,2], where using this we have been able to obtain the invariant measure of these maps for small k and thereof it is shown that these maps have the same Kolmogorov-Sinai entropy or equivalently Lyapunov characteristic exponent of the maps [1,2].
…”
mentioning
confidence: 99%
“…
AbstractWe present hierarchy of one and many-parameter families of elliptic chaotic maps of cn and sn types at the interval [0,1]. It is proved that for small values of k the parameter of the elliptic function, these maps are topologically conjugate to the maps of references [1,2], where using this we have been able to obtain the invariant measure of these maps for small k and thereof it is shown that these maps have the same Kolmogorov-Sinai entropy or equivalently Lyapunov characteristic exponent of the maps [1,2].
…”
mentioning
confidence: 99%
“…A recent attempts in introducing the hierarchy of chaotic maps with their invariant measure [16,17,22,23,24] allows us to advance in answering to a question how to define non-ergodic maps and what are the condition for non-ergodicity in these types of system.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the calculation of the invariant measure in our pervious papers [16,17,22,23,24], we present here it for the piecewise chaotic map. In order to prove that measure satisfied equation (3-1), we consider the conjugate map;…”
Section: Appendix Amentioning
confidence: 95%
“…One-parameter families of chaotic maps of the interval [0, 1] with an invariant measure can be defined as the ratio of polynomials of degree N [Jafarizadeh et al, 2001]:…”
Section: Composition Of Trigonometric Chaotic Mapsmentioning
confidence: 99%
“…This paper aims to introduce a new chaotic algorithm which has the advantages of high-level security, large key space and the acceptable encryption speed. Since digital images are usually represented as twodimensional arrays, we present algorithm based on Trigonometric Chaotic Maps and their Composition [Jafarizadeh et al, 2001]. A diffusion process is performed to confuse the relationship between cipher-image and plain-image.…”
Section: Introductionmentioning
confidence: 99%